Low-frequency attenuation signal absorption performance of thin-film acoustic metamaterials - Xu Jingcheng; Chen Changzheng (Acta Acustica)
Considering that thin film acoustic metamaterials have many special properties that natural materials and traditional materials do not possess, the low-frequency attenuation signal absorption performance of thin film acoustic metamaterials is studied. Prepare thin film acoustic metamaterials using raw materials such as silicone, calculate the basic law of low-frequency attenuation signal absorption based on this material, and determine the acoustic parameters of thin film acoustic metamaterials through calculation. Using the obtained acoustic parameters as inputs, a finite element numerical model of thin film acoustic metamaterials is used to analyze the low-frequency attenuation signal absorption performance under changes in porosity, thickness, density, size, tension, parameter error, and frame material and mass width in contact area with the thin film. The experimental results show that when the porosity is 95%, the thickness is 11, the variable length is 16 mm, the tension force is 160 N/m, and the contact area between the mass block and the film is 5.5 mm2, the absorption effect of low-frequency attenuation signals is the best. The frame material and elastic modulus have little effect on the absorption performance of the thin film acoustic material.